Functional Outcomes of Inpatient Prehabilitation for Pseudomyxoma Peritonei: A Case Report - Chung Khian, Yew; Chiann Ni, Thiam; Heng Jee, See; Nor Hanan, Nasir; Muhammad Zafril Izhar, MZ; Siti Nur Aida, Zailan; Nur Syafariza, Izmin; Chau Chung, Chai (Clinical Research Centre Hospital Raja Permaisuri Bainun, 2025)
Introduction : Pseudomyxoma peritonei (PMP) is a rare but debilitating abdominal cancer that can cause significant functional limitations and quality of life. Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) are the standard treatments for PMP. Prehabilitation is a novel approach to optimize the physical and psychological status of patients prior to cancer treatment. This case report aims to evaluate the functional outcome of a two-week inpatient prehabilitation for a 47 years old, Malay lady with PMP secondary to mucinous neoplasm planning for CRS and HIPEC using standardized measures of health-related quality of life and functional capacity.